Estudo fitoquímico e atividade biológica das raízes de Apodanthera congestiflora Cogn. (Cucurbitaceae) - Pereira, Helimarcos Nunes (2017)
The present work describes the first phytochemical studies, biological evaluation and physical-chemical characterization of Apodanthera congestiflora Cogn roots. This cucurbitacea popularly known as ―cabeça de negro‖ is cited in ethnobotanical studies for its analgesic, anti-inflammatory, depurative, antiparasitic and antimicrobial activities. The preparation of an aqueous extract by decoction (EAN-Ac) and others by accelerated extraction with the solvents hexane, acetate and ethanol (FH-Ac, FA-Ac, FE-Ac) was carried out. The vegetal drug (DV-Ac) and EAN-Ac were submitted to quality control through traditional pharmacopoeial methods and instrumental techniques. Both were within the parameters recommended by the official compendia. The extracts underwent a preliminary phytochemical evaluation, demonstrating the presence of saponins, polysaccharides and alkaloids. Specifically, EAN-Ac and FA-Ac presented quantification of polyphenols, flavonoids and tannins. In the evaluation of the biological activity and phytochemical prospecting the bioguided study model was followed, guided by the anti-inflammatory activity. EAN-AC-Ac and FA-Ac exhibited anti-inflammatory activity. The latter also presented antimicrobial activity against strains of S. aureus and C. albicans and presented a considerable toxicological potential. The FA-Ac was selected and isolated (through chromatographic techniques) and identified by spectroscopic techniques (IV, 1H and 13C) 2 esterified phenolic acids, 2- propenoic acid ferulate, 3- (4- hydroxy-3-methoxyphenyl) decyl ester (Ac-1) and p cinnamate 2-propenoic acid, 3- (4-hydroxyphenyl) decyl ester (Ac-2). In addition to the latter, 3 glycosylated triterpenoids of the norcucurbitacin class were purified: 29-nor 1,2,3,4,5,10-dehydro-25-O-acetyl-2-O-β-D-glucopyranosyl-3 , 16α, 20 (R) -trihydroxy 11,22-dioxocurbite-6.23, diene (Ac-3), known as Cayaponoside A; (R) -trihydroxy 11,22-dihydro-25-O-acetyl-2-O-β-D-glucopyranosyl-3,16α, 20β- (Ac-4), known as Fevicordine A and 19-norcolesta-1,3,5,10-6-tetraene-11,22-dione, 2- (β-D glucopyranosyl) -6- 3, 16, 20,25-tetrahydroxy-4,9,14-trimethyl- (9β, 16α), known as Cayaponoside C. The phenolic esters isolated in the present study are already widely known in the literature, but the triterpenes obtained belong to a class with few studies described and, in general, the isolation of these chemical compounds is pioneer in the mentioned species. In addition, the EAN-AC-Ac, obtained by decoction, did not present evidence of toxicity, inferring that A. congestiflora is safe for use by the population in the form of decoction, but with the proper criterion, since it presents in its constitution active principles potentially toxic.